EVALUASI HASIL DUA POPULASI GALUR-GALUR F7 HASIL PERSILANGAN GROBOGAN x KM 19 DAN GROBOGAN x KM 25 (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Productivity of soybean in Indonesia is still low due mainly to environmental and genetic factors as well as improper cultural practices. The productivity can be increased; however, by the improvement of soybean varieties and developing new varieties. This study was intended to compare yield potential of two F7 populations derived from crossing Grobogan x KM 19 and Grobogan x KM 25. A field experiment was conducted in the Factulty of Agriculture Experiment Station, Riau University located in Pekanbaru from April to July 2021. Nineteengenotypes consisting of eight F7 lines each from crosses of Grobogan x KM 19, and Grobogan x KM 25, included their three parents were each planted in a 3 m by 2 m plot with 3 replications. Data obtained from this study were analyzed by usinganalysis of variance and then were tested by the Dunnet test at the 5% level. To compare the two populations, t-testprocedure was applied.The results showed significant difference of 19 genotypes on all characters tested except for plant height, while the t-test imposed to the two populations did not show significant differences for the 11 tested characters.Keywords: soybean genotypes, productivity, t Test